The impact of school leadership and school environment on teacher job satisfaction in Latin America - Cynthia Martínez-Garrido (Arizona State University, 2017)
The research on Educational Effectiveness has identified teachers' work satisfaction as a key element for the development of effective teaching. However, rather the number of studies analyzing the effect of teachers' job satisfaction on student performance, there is less research available to understand how teacher satisfaction is developed and what it depends on. The objective of this research is to know the relationship between teacher's job satisfaction, school management and climate. To achieve our aim, we conduct a multilevel analysis of the information provided by the teachers of 5,733 schools in 15 Latin American countries participating in UNESCO's Third Regional Comparative and Explanatory Study (TERCE). Our results show that the work environment, the classroom climate and management support to teachers are the variables that have most impact on the level of job satisfaction of teachers in Latin America.